2017
DOI: 10.1111/hsc.12489
|View full text |Cite
|
Sign up to set email alerts
|

Profile of consumers and their partners of a perinatal and infant mental health (PIMH) service in Australia

Abstract: The perinatal period is a time of great vulnerability for many women, in particular those with a range of psychosocial vulnerabilities and mental health risk factors. This and mental health issues (30.81%). This study contributes to our understanding of the profile of vulnerable women in the perinatal period, and in particular contributes to the literature by highlighting that in addition to depression, anxiety, self-harm and trauma are also significant in PIMH service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Identified prevalence rates of trauma in this group are much higher than rates in the general community, where for example, studies have found lifetime prevalence of interpersonal trauma or childhood trauma between 11.8% (25) and 27.7% (11) in pregnant women in general antenatal settings. Women experiencing perinatal mental illness and receiving community-based care have been found to have rates of childhood trauma closer to the current study, between 34% (26) and 60% (27). This finding suggests a possible relationship between trauma prevalence and severity of perinatal mental illness, and a need for greater understanding of this relationship.…”
Section: Discussionsupporting
confidence: 66%
“…Identified prevalence rates of trauma in this group are much higher than rates in the general community, where for example, studies have found lifetime prevalence of interpersonal trauma or childhood trauma between 11.8% (25) and 27.7% (11) in pregnant women in general antenatal settings. Women experiencing perinatal mental illness and receiving community-based care have been found to have rates of childhood trauma closer to the current study, between 34% (26) and 60% (27). This finding suggests a possible relationship between trauma prevalence and severity of perinatal mental illness, and a need for greater understanding of this relationship.…”
Section: Discussionsupporting
confidence: 66%
“…For many women the perinatal period is a time of great social, emotional and physical vulnerability that can impact profoundly on their sense of identity, mental health and well‐being (Austin, Kildea, & Sullivan, ; Doucet, Letourneau, & Blackmore, ; Healey et al., ; Monzon, di Scalea, & Pearlstein, ). Estimates indicate that between 15% and 25% of women have a mental health problem during this time (Bauer, Parsonage, Knapp, Lemmi, & Adelaja, ; Khan, ; McCauley, Elsom, Muir‐Cochrane, & Lyneham, ; Schmied et al., ), most commonly depressive and anxiety disorders (Coates, Saleeba, & Howe, ; Leach, Christensen, & Mackinnon, ; Sidebottom, Hellerstedt, Harrison, & Hennrikus, ). Perinatal anxiety is associated with high rates of child birth fear (Halvorsen, Nerum, Øian, & Sørlie, ; Räisänen et al., ; Rouhe, Salmela‐Aro, Gissler, Halmesmäki, & Saisto, ), which can be conceptualised as a form of anxiety (Hall et al., ), and affects around 25% of pregnant women in Australia (O'Connell, Leahy‐Warren, Khashan, Kenny, & O'Neill, ; Toohill, Fenwick, Gamble, & Creedy, ).…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T 5 with a history of personal, familial or spousal mental illness are vulnerable to depression during pregnancy (Coates et al, 2018). Parental mental disorders have been recognized as a risk factor for a variety of psychiatric disorders in the offspring (Rasic et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%